Phase-shifted Series Resonant Converter with Zero Voltage Switching Turn-on and Variable Frequency Control - Mohamed Salem; Awang Jusoh; Nik Rumzi Nik Idris; Tole Sutikno; Yonis.M.Yonis Buswig (Institute of Advanced Engineering and Science, 2017)
This paper presents a phase shifted series resonant converter with step up high frequency transformer to achieve the functions of high output voltage, high power density and wide range of Zero Voltage Switching (ZVS). In this approach, the output voltage is controlled by varying the switching frequency. The controller has been designed to achieve a good stability under different load conditions. The converter will react to the load variation by varying its switching frequency to satisfy the output voltage requirements. Therefore in order to maintain constant output voltage, for light load (50% of the load), the switching frequency will be decreased to meet the desired output, while for the full load (100%) conditions, the switching frequency will be increased. Since the controlled switching frequency is limited by the range between the higher and lower resonant frequencies , the switches can be turned on under ZVS. In this study, a laboratory experiment has been conducted to verify the effectiveness of the system performance.